Key considerations on the potential impacts of the COVID-19 pandemic on antimicrobial resistance research and surveillance. (27th March 2021) - Rodríguez-Baño, Jesús; Rossolini, Gian Maria; Schultsz, Constance; Tacconelli, Evelina; Murthy, Srinivas; Ohmagari, Norio; Holmes, Alison; Bachmann, Till; Goossens, Herman; Canton, Rafael; Roberts, Adam P; Henriques-Normark, Birgitta; et al.
Abstract: Antibiotic use in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) patients during the COVID-19 pandemic has exceeded the incidence of bacterial coinfections and secondary infections, suggesting inappropriate and excessive prescribing. Even in settings with established antimicrobial stewardship (AMS) programmes, there were weaknesses exposed regarding appropriate antibiotic use in the context of the pandemic. Moreover, antimicrobial resistance (AMR) surveillance and AMS have been deprioritised with diversion of health system resources to the pandemic response. This experience highlights deficiencies in AMR containment and mitigation strategies that require urgent attention from clinical and scientific communities. These include the need to implement diagnostic stewardship to assess the global incidence of coinfections and secondary infections in COVID-19 patients, including those by multidrug-resistant pathogens, to identify patients most likely to benefit from antibiotic treatment and identify when antibiotics can be safely withheld, de-escalated or discontinued. Long-term global surveillance of clinical and societal antibiotic use and resistance trends is required to prepare for subsequent changes in AMR epidemiology, while ensuring uninterrupted supply chains and preventing drug shortages and stock outs. These interventions present implementation challenges in resource-constrained settings, making a case for implementation research on AMR. Knowledge and support for these practices will come from internationally coordinated, targeted research on AMR, supporting the preparation for future challenges from emerging AMR in the context of the current COVID-19 pandemic or future pandemics.